Pengaruh Current Rasio (CR) dan Return On Asset (ROA) Terhadap Harga Saham PT. Waskita Karya (Persero) Tbk - Istiqamah Istiqamah; M. Rimawan; Alwi Alwi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study explores the influence of Current Ratio (CR) and Return On Asset (ROA) on the share price of PT. Waskita Karya (Persero) Tbk. The data used is the financial statements of a certain period. The regression analysis method is used to assess the relationship between CR, ROA, and stock price variables. The results of the study show that these two factors have a significant influence on the company's stock price. The implication of these findings is the importance of liquidity management and asset efficiency in influencing stock market value.